2021
DOI: 10.1186/s12886-021-01932-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ocular biometric parameters and optimal model of anterior chamber depth regression in 28,709 adult cataract patients in China using swept‐source optical biometry

Abstract: Background The purpose of this study was to evaluate the ocular biometric parameters in adult cataract patients from China and create an anterior chamber depth (ACD) regression model. Methods The ocular biometric records of 28,709 right eyes of cataract surgery candidates who were treated at Aier Eye Hospitals in nine cities from 2018 to 2019 were retrospectively analyzed. All measurements were taken with IOLMaster 700. We included patients who wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 35 publications
8
25
1
Order By: Relevance
“…Previously, various studies reported about the relationship between age and ocular biometric parameters, and of those, IOLMaster 700 was used in 5 studies from 2 countries (China and Israel). 1,5,[19][20][21][22][23][24][25][26][27][28][29][30][31] Age was shown to have a positive correlation with LT and AK and a negative correlation with AL, ACD, and WTW in Chinese patients, which were consistent with our data. 1 Meng et al reported that older age, lower AK, shorter WTW, and shallower ACD showed higher angle a or angle k in Chinese patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previously, various studies reported about the relationship between age and ocular biometric parameters, and of those, IOLMaster 700 was used in 5 studies from 2 countries (China and Israel). 1,5,[19][20][21][22][23][24][25][26][27][28][29][30][31] Age was shown to have a positive correlation with LT and AK and a negative correlation with AL, ACD, and WTW in Chinese patients, which were consistent with our data. 1 Meng et al reported that older age, lower AK, shorter WTW, and shallower ACD showed higher angle a or angle k in Chinese patients.…”
Section: Discussionsupporting
confidence: 92%
“…With the introduction of premium IOLs, such as toric and multifocal IOLs, it has become increasingly important to fully understand the factors related to ocular biometric parameters. 1,2 The ocular biometric parameters are interrelated and tend to change with age. [3][4][5] The parameters are different according to the ethnicity and region.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the AL was < 22.5 mm and the depth of the ACD was < 2.5 mm in both groups. Previous studies by Lei et al (19) showed that nearly 12% of Chinese elderly participants had an ACD < 2.5 mm. Therefore, the prevention and treatment of glaucoma should be strengthened for the elderly population with similar ocular biometry, such as short AL.…”
Section: Discussionmentioning
confidence: 92%
“…[ 5 ] On the other hand, LT is the main factor that affects anterior chamber depth (ACD). [ 6 ] Therefore, we should pay more attention to the anterior chamber parameters of adult cataract patients and be alert to the PACG. In routine clinical use, gonioscopy is the most common method to evaluate the anterior chamber angle, which is subjective and highly dependent on the examiner’s judgement and experience.…”
Section: Introductionmentioning
confidence: 99%